Pelatihan Pengolahan Sampah Plastik Menjadi Ecobrick di SDN 2 Cikalang Kota Tasikmalaya - Dea Aditria; Anuy Nurofiat; Calista Angelina; Analisa Salsabila; Kamelia Pemiliani; Siti Faridah N A; Nur Azmi Syahla; Fathiah Qolbu; Alia Dwi Andini; Rifa Ajrina Faisal; Rihan Subagja; Nissa Noor Annashr (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The issue of waste, especially plastic waste, has become a crucial problem in Indonesia, leading to ecosystem damage and environmental pollution. SDN 2 Cikalang, located in Tasikmalaya City, is one of the schools that has not yet implemented optimal plastic waste management. An Ecobrick outreach program was conducted to enhance the knowledge of fifth-grade students about plastic waste management through Ecobrick innovation. An Ecobrick is a plastic bottle filled tightly with plastic waste, which can be used as a construction material to replace bricks. This study aims to evaluate the effectiveness of the Ecobrick outreach program in increasing students' knowledge of plastic waste management. The research methods included pre-test, material delivery, hands-on practice, and post-test. The evaluation results showed a 45% increase in students' knowledge, with a significant difference between pre-test and post-test scores (p value = 0.000). This indicates that a hands-on education approach is effective in improving students' understanding of plastic waste management through Ecobrick.